2011
DOI: 10.1158/0008-5472.can-11-0608
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Sequence and Expression Analysis in Breast Tumors by Deep Sequencing

Abstract: MicroRNAs (miRNAs) regulate many genes critical for tumorigenesis. We profiled miRNAs from 11 normal breast tissues, 17 non-invasive, 151 invasive breast carcinomas, and 6 cell lines by in-house-developed barcoded Solexa-sequencing. miRNAs were organized in genomic clusters representing promoter-controlled miRNA expression and sequence families representing seed-sequence-dependent miRNA-target regulation. Unsupervised clustering of samples by miRNA sequence families best reflected the clustering based on mRNA … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
338
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 325 publications
(355 citation statements)
references
References 46 publications
14
338
0
2
Order By: Relevance
“…In this study, genes with inversely related profiles to miR-210 included BRCA1, FANCD, FANCF, PARP1, E-cadherin, and Rb1, which were all activated in DCIS and downregulated in the invasive carcinoma. In our study, we found that miR-210 and miR-18a were significantly increased in IDC compared with DCIS, which is consistent with the changes described by Volinia and colleagues in the invasive transition (25,26). However, we did not find significant changes in DCIS when compared with normal breast or CUBs.…”
Section: Er-bbb Casesupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, genes with inversely related profiles to miR-210 included BRCA1, FANCD, FANCF, PARP1, E-cadherin, and Rb1, which were all activated in DCIS and downregulated in the invasive carcinoma. In our study, we found that miR-210 and miR-18a were significantly increased in IDC compared with DCIS, which is consistent with the changes described by Volinia and colleagues in the invasive transition (25,26). However, we did not find significant changes in DCIS when compared with normal breast or CUBs.…”
Section: Er-bbb Casesupporting
confidence: 92%
“…Our data complement a recent profiling study using deep sequencing of miRNAs in DCIS revealed that several miRNAs (including miR-210) were decreased in the transition from normal breast to DCIS, but increased in the transition from DCIS to IDC (25,26). In this study, genes with inversely related profiles to miR-210 included BRCA1, FANCD, FANCF, PARP1, E-cadherin, and Rb1, which were all activated in DCIS and downregulated in the invasive carcinoma.…”
Section: Er-bbb Casesupporting
confidence: 85%
“…The miRNA content was not significantly different between groups (Fig. S2B) and comparable with other tissues (25). We reviewed the sequence alignments of unannotated reads to the genome and found no evidence of novel highly expressed miRNA genes.…”
Section: Significancementioning
confidence: 61%
“…We reviewed the sequence alignments of unannotated reads to the genome and found no evidence of novel highly expressed miRNA genes. We also analyzed miRNA sequence variation as described previously (25)(26)(27) and found no novel SNPs in positions known to affect miRNA biogenesis or their target mRNA regulation (Dataset S1).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation